2017
DOI: 10.1007/s12640-016-9697-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Alterations and the Protective Effect of Punicalagin Against Glutamate-Induced Oxidative Toxicity in HT22 Cells

Abstract: Oxidative stress is involved in many neurological diseases, including Alzheimer's disease. Punicalagin (PC) is a hydrolysable polyphenol derived from Punica granatum and a potent antioxidant. In this study, the neuroprotective effect of PC on glutamate-induced oxidative stress was evaluated in the mouse hippocampal cell line, HT22. PC treatment protected HT22 cells from glutamate-induced cell death in a concentration-dependent manner, potentially attenuated glutamate-induced intracellular reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Unlikely, Ran which reduced these alterations without normalization indicating the superior antioxidant property of PCG to the standard drug; Ran. Previous studies also displayed the antioxidant property of PCG [11,12,[23][24][25].…”
mentioning
confidence: 84%
“…Unlikely, Ran which reduced these alterations without normalization indicating the superior antioxidant property of PCG to the standard drug; Ran. Previous studies also displayed the antioxidant property of PCG [11,12,[23][24][25].…”
mentioning
confidence: 84%
“…Oxidative stress promotes neurotoxicity by increasing amyloid beta (A β ) aggregation concomitantly with inflammatory events such as reactive oxygen species (ROS) production [ 3 ]. Additionally, excess extracellular glutamate levels have been found to correlate with the development of neurodegenerative disorders by triggering oxidative glutamate damage, preventing the intracellular antioxidant synthesis, and ultimately leading to ROS accumulation [ 4 ]. The overproduction of ROS and A β causes a feedback loop that results in synaptic dysfunction, as well as mitochondria-mediated apoptosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This disturbs the membrane integrity and Ca 2+ homeostasis to produce hepatocellular damage [36]. The use of phytochemicals with antioxidant activity can offer protection against the oxidative damage [37]. The present investigation revealed that an ethanolic extract of A. baccifera (EEAB) significantly attenuated the CCl 4 induced oxidative stress by augmenting the endogenous antioxidant levels.…”
Section: Discussionmentioning
confidence: 69%